Faktor Pendukung dan Penghambat Pemberdayaan Masyarakat dalam Menanggulangi Kenakalan Remaja - Syaria, Intan; Alhadi, Zikri (Policy, Law and Political Research Center, 2024)
Juvenile delinquency is a criminal phenomenon that often occurs in society, therefore the government has issued several regulations for law violators which will ensnare perpetrators, in this case teenagers, if they violate the following regulations: Drug Abuse, regulated in article 127 paragraph (1) Law Number 35 of 2009 concerning Narcotics, that every abuser of: Category I Narcotics for himself, shall be punished with a maximum imprisonment of 4 (four) years. Class II narcotics are punishable by a maximum imprisonment of 2 (dual) years. Class III narcotics for himself, is punishable by a maximum imprisonment of 1 (one) year. This research discusses the supporting and inhibiting factors for community empowerment in tackling juvenile delinquency. Study: youth organizations in Jorong Pintu Rayo Nagari Tanjung Barulak. The government in Nagari Tanjung Barulak together with youth organizations designed various youth group empowerment programs to engage teenagers in things that are more positive and beneficial for society and themselves. Therefore, this research was carried out to find out how community empowerment is in dealing with juvenile delinquency. Study: youth organizations in Jorong Pintu Rayo Nagari Tanjung Barulak. This research uses a descriptive qualitative approach using data collection techniques in the form of interviews and documentation. The theory of community empowerment used in this research is the theory presented by Jim Ife (1995)